Pierwszy raz w ciemnym kinie – filmowe reminiscencje w twórczości Krystyny Kofty - Witczak, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article is an attempt to interpret the cinema experience from the perspective of contemporary theories of somatic reception. Attention is drawn to the formal aspect of two examples of cinema experiences by a contemporary Polish writer (Krystyna Kofta). An important element of her work is sharing impressions, especially in relation to the description of everyday life. The analysis includes the comparison of two cinema episodes – a girl fascinated by the first encounter with this medium and an adult woman terrifed by the claustrophobic atmosphere of the cinema.